NEW MEDIA DAN KOMUNIKASI ANTARBUDAYA: (KAJIAN DAMPAK NEW MEDIA PADA KOMUNIKASI ANTARBUDAYA DALAM KONTEKS GLOBAL) - nikmah suryandari (Jurnal Sosioteknologi, 2021)
The rapid development of new media has been the main force accelerating the trend of globalization in human societyin recent decades. New media has brought human interaction and society to a highly interconnected and complex level,but at the same time challenged the very existence of intercultural communication in its traditional sense. It is under thiscircumstance that we see more and more scholars becoming involved in the investigation of the relationship between new media and intercultural communication. Emerging topical areas in this line of research mainly include three categories: (1) the impact of national/ethnic culture on the development of new media, (2) the impact of new media on cultural/social identity, and (3) the impact of new media (especially social media) on different aspects of intercultural communication (e.g., intercultural relationships, intercultural adaptation, and intercultural conflict). This paper discusses this trend of research on the relationship between new media and intercultural communication.